Pemeriksaan Formalin Pada Bakso Ayam Yang Dijual Di Beberapa Pasar Kota Bengkulu - Nita Anggreani; Eka Nurdianty Anwar; Helda Afri yulyani (CV. Multi Kreasi Media, 2022)
-Chicken meatballs are a type of meatball that uses chicken meat as the main processed ingredient and is very popular with the public because the price is relatively cheap. Chicken meatball traders in the market usually sell their products without using ice coolers for preservation. This raises concerns if these traders use food preservatives from dangerous chemicals, one of which is formalin. This study aims to examine whether there is formalin content in chicken meatball products sold in markets in the city of Bengkulu. Six samples of chicken meatballs were purchased from Panorama Market, Pagar Dewa Market, and Bengkulu City Sunday Market. The qualitative analysis method used was a color test with chromotropic acid, while the quantitative analysis used titration. The results showed that of the 6 samples of chicken meatballs examined, all were negative for formaldehyde. Keywords: formalin, chicken meatballs, dangerous chemical preservatives.